If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + 41 + -5x = 3 + -8x + 2 Reorder the terms: 41 + 3x + -5x = 3 + -8x + 2 Combine like terms: 3x + -5x = -2x 41 + -2x = 3 + -8x + 2 Reorder the terms: 41 + -2x = 3 + 2 + -8x Combine like terms: 3 + 2 = 5 41 + -2x = 5 + -8x Solving 41 + -2x = 5 + -8x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '8x' to each side of the equation. 41 + -2x + 8x = 5 + -8x + 8x Combine like terms: -2x + 8x = 6x 41 + 6x = 5 + -8x + 8x Combine like terms: -8x + 8x = 0 41 + 6x = 5 + 0 41 + 6x = 5 Add '-41' to each side of the equation. 41 + -41 + 6x = 5 + -41 Combine like terms: 41 + -41 = 0 0 + 6x = 5 + -41 6x = 5 + -41 Combine like terms: 5 + -41 = -36 6x = -36 Divide each side by '6'. x = -6 Simplifying x = -6
| 1/4x+1/4x=8 | | k+4(2k-7)=-100 | | (3/4)/(5/7) | | 2-5p-3p=-6 | | 3/4/5/7 | | -2m-24=0 | | 2-5p-4p=-6 | | 48/60 | | y+1=6/5x+18/5 | | a+4+2a=-8 | | -8n+-4=-28 | | (-3)*(-13)+(-41)= | | -11+2(x-3)+x=3(x-3)-8 | | 1=2+1/2 | | 5(3x+2)=2(2x+3) | | 5(x-2)-3=2x+3(-3+x) | | -5(7+7n)=-280 | | x/2+6=3x-12+x/2 | | 12x+15=-2 | | 3x+7=6x+9 | | 8n-4=-28 | | -6x-2x=-8 | | Y-2=4/9(x-3) | | 5x+5+1=-9 | | b+7+6=19 | | 5/6-1/3=-2 | | 3x+4x=12+16 | | -3x+5=6x+24 | | 4-4x-4=-20 | | 2-7x=-11x-5 | | 6y+4y=9y+8 | | 3x-12+5x+4=5x-28+7x+8 |